Analysis of Cooperative Learning Model in Sociology Education as an Effort to Develop 21st Century 4C Skills - Ceni Nur Inayah; Wilodati Wilodati; Sri Wahyuni (Faculty of Social Science, Universitas Negeri Semarang, 2023)
The rapid advancement of information technology and automation marks the 21st century. These conditions encourage an increase in the quality of human resources, one of which is through the realm of education by emphasizing mastery of 4C skills (communication, collaboration, critical thinking and problem-solving, and creative thinking). Cooperative learning is a learning model that emphasizes cooperation and collaboration among students in a study group to solve problems and achieve goals collectively, effectively, and efficiently. The cooperative learning model is relevant to be applied in sociology learning because it emphasizes aspects of collaboration that correlate with sociology learning. Writing this article uses a qualitative approach with the literature study method and data collection techniques by collecting library data from reference books, articles, journals, and other relevant documents—technical data analysis using content analysis techniques. Based on the results of a literature search, it can be seen that the cooperative learning model applied in sociology learning can be an alternative effort to develop 4C skills in students to face the complex 21st century because it emphasizes aspects of collaboration and helps hone communication skills, critical thinking, and creative thinking.